Transition of care in a Danish context: translation, cross-cultural adaptation and content validation of CTM-15 and PACT-M - Merete Ajstrup; Caroline Trillingsgaard Mejdahl; David Høyrup Christiansen; Lene Kongsgaard Nielsen (SpringerOpen, 2024)
Abstract Background Transition of care from hospitalisation to home is a complex process with potential patient safety risks, especially for patients with multimorbidity. Traditionally, the quality of transition of care has been evaluated primarily through readmission rates. However, interpreting the readmission rates presents challenges, and readmission rates fail to capture the patient's perspective on the quality of the care transition. Insight into the patient's experience with their care or a health service can be provided through the use of patient-reported experience measures (PREMs), and the two PREMs Care Transitions Measure 15 (CTM-15) and Partners at Care Transitions Measure part 1 and 2 (PACT-M1 and PACT-M2) assess on the quality of transition of care from the patients' perspective. The aim of this study was to translate, culturally adapt, and assess content validity of CTM-15, PACT-M1, and PACT-M2 for Danish-speaking patients with multimorbidity. Methods A two-step approach was used for content validation, involving cognitive debriefing and interviews with patients, representing the target group, as well as quantitative data collection from healthcare professionals representing all three sectors of the Danish healthcare system. The patients were systematically interviewed regarding the aspects of content validity; comprehensibility, relevance, and comprehensiveness. The healthcare professionals assessed the relevance and comprehensiveness of each item through questionnaires, allowing the calculation of a content validity index (CVI). An item CVI ≥ 0.78 is considered good. Results The results of the qualitative data indicated that both CTM-15 and the PACT-M questionnaires were considered relevant, and comprehensible, and comprehensive to the target group. The CVI computed at item level determined that PACT-M1 and PACT-M2 demonstrated excellent content validity among the healthcare professionals, whereas the CVI for two items of the CTM-15 fell below the threshold value for "good". Conclusion The Danish versions of the PACT-M questionnaires demonstrated good content validity, and the CTM-15 demonstrated acceptable content validity based on qualitative data from patients and quantitative data from healthcare professionals. Further validation of the questionnaires, by assessing their construct validity and reliability is recommended.